On the use of rhodium mirrors for optical diagnostics in ITER - Mertens, Philippe; Boman, Romain; Dickheuer, Sven; Krasikov, Yury; Krimmer, Andreas; Leichtle, Dieter; Liegeois, Kim; Linsmeier, Christian; Litnovsky, Andrey; Marchuk, Oleksander; Rasinski, Marcin; De Bock, Maarten (Fusion engineering and design, 2019)
The first mirrors of optical diagnostics in ITER are exposed to high radiation and fluxes of particles which escape the plasma, in the order of 1020 m−2s−1. At the position of the mirror, the flux may still reach about 1018 m−2s−1. First mirrors are thus the most vulnerable in-vessel optical components, being subject to erosion, esp. by fast charge-exchange neutrals, or to deposition of impurities at flux rates which can reach 0.05 nm/s. The material selected for the reflecting surface must combine a high optical reflectivity in a wide spectral range and a sufficient resistance to physical sputtering during normal operation and during mirror cleaning discharges, if any is installed. Rhodium (103Rh) was identified early as a possible or even promising candidate. It combines several attractive properties, for instance a mass which leads in most cases to low sputtering yields together with an optical reflectance (RRh≈75%) which is much higher than of some other options. RRh is insensitive to large temperature changes. Rhodium is fairly inert and its low oxidation is an appreciable advantage in case of steam ingress events. The core-plasma CXRS diagnostic in ITER (UPP 3) have now turned to Rh as a baseline. The aim is to procure monocrystalline rhodium (SC-Rh) to mitigate the increase of the diffuse reflection with the damage due to physical sputtering.